The effects of inflammation on connexin 43 in chronic Chagas disease cardiomyopathy - Barreto, Breno Cardim; Neves, Maria Vitória Gomes das; Cardoso, Carine Machado Azevedo; Meira, Cássio Santana; Daltro, Pâmela Santana; Figueira, Cláudio Pereira; Santos, Girlaine Café; Silva, Daniela Nascimento; Távora, Fábio; Neto, João David de Souza; Macambira, Simone Garcia; Lampe, Paul D.; et al. (Frontiers in Immunology, 2024)
Background: Cardiac arrhythmias are the main cause of sudden death due to Chronic Chagasic Cardiomyopathy (CCC). Here we investigated alterations in connexin 43 (Cx43) expression and phosphorylation in cardiomyocytes as well as associations with cardiac arrhythmias in CCC. Methods:C57Bl/6 mice infected with Trypanosoma cruzi underwent cardiac evaluations at 6 and 12 months after infection via treadmill testing and EKG. Histopathology, cytokine gene expression, and distribution of total Cx43 and its phosphorylated forms Cx43 S368 and Cx43 S325/328/330 were investigated. Human heart samples obtained from subjects with CCC were submitted to immunofluorescence analysis. In vitro simulation of a pro-inflammatory microenvironment (IL-1β, TNF, and IFN-γ) was performed in H9c2 cells and iPSC-derived cardiomyocytes to evaluate Cx43 distribution, action potential duration, and Lucifer Yellow dye transfer. Results: Mice chronically infected with T. cruzi exhibited impaired cardiac function associated with increased inflammation, fibrosis and upregulated IL-1β, TNF, and IFN-γ gene expression. Confocal microscopy revealed altered total Cx43, Cx43 S368 and Cx43 S325/328/330 localization and phosphorylation patterns in CCC, with dispersed staining outside the intercalated disc areas, i.e., in lateral membranes and the cytoplasm. Reduced co-localization of total Cx43 and Ncadherin was observed in the intercalated discs of CCC mouse hearts compared to controls. Similar results were obtained in human CCC heart samples, which showed Cx43 distribution outside the intercalated discs. Stimulation of human iPSC-derived cardiomyocytes or H9c2 cells with IL-1β, TNF, and IFN-γ induced alterations in Cx43 localization, reduced action potential duration and dye transfer between adjacent cells. Conclusion: Heart inflammation in CCC affects the distribution and phosphorylation pattern of Cx43, which may contribute to the generation of conduction disturbances in Chagas disease.